THE EFFECTIVENESS OF USING KAHOOT! AS A MEDIA TO IMPROVE STUDENTS' READING COMPREHENSION IN NARRATIVE TEXT (RETAIN, 2020)
The researcher's intention in doing this research was to know if there is a substantial difference in the comprehension of students reading in a narrative text after treatment with Kahoot! as a platform for 10th graders at one of the Senior High Schools in Lamongan. The method used was quasi-experimental pretest-posttest research design. There were two classes of this research, and they are X Social 1 as experimental class which has 20 students and X Social 2 as control class which also has 20 students. The teaching process done in control class was using textbook as a media, while in experimental class was using Kahoot!. The research instrument used was a reading comprehension test. The researcher utilized Paired Sample T-test in SPSS 26 to analyze the results. It shows that the significant value was .000, which was less than the significant level 0.05. Therefore, this indicated that there was difference between the pre-test and post-test score of students. Then, to show the specific significant value of experimental treatment, the researcher calculate the effect size which value was 0.9 which means the treatments given successfully gave moderate effect to the experimental class. It can be concluded that the use of Kahoot ! as a media for tenth graders of one of Senior High Schools in Lamongan influences their score in reading comprehension in narrative text. Keywords: Kahoot!, Media, Reading Comprehension, Narrative Text.